Does a Free Trade Agreement’s Impact on the Export of Halal Food to OIC Countries Matter? Evidence from Indonesia - Masruri Muchtar; Hafid Asy’ari; Ahmad Rodoni; Euis Amalia; Muhamad Nadratuzzaman Hosen (Faculty of Economic and Business, 2024)
Research Originality: The second-largest organisation after the UN, with a population of 24.4% worldwide, makes OIC countries a potential market. This paper contributes to the existing literature on trade within them by focusing on crucial aspects of the trade agreement's impact on the halal food industry.Research Objectives: This study examines the influence of a free trade agreement (FTA) on Indonesian halal food exports.Research Methods: Using panel data from 23 countries spanning the period from 2003 to 2019, the paper employs the gravity model to assess the impact of the FTA and other variables on Indonesian halal food exports to OIC countries.Empirical Results: The findings indicate that Indonesian food exports to OIC countries with FTAs experience a notable 68% increase compared to those without such agreements. The study reveals GDP, population size, trade openness, and exchange rate positively affect food exports to OIC countries. However, trading partners' distance and entry time exhibit a negative correlation.Implications: This research holds significance for the Indonesian government as it provides valuable insights for considering the acceleration of trade agreement ratification with OIC countries. JEL Classification: F13, F47, C68How to Cite:Muchtar, M., Hafid, A., Rodoni, A., Amalia, E., & Hosen, M. N. (2024). Does a Free Trade Agreement’s Impact on the Export of Halal Food to OIC Countries Matter? Evidence from Indonesia. Etikonomi, 23(1), 147 – 166. https://doi.org/10.15408/etk.v23i1.32951.